(untitled) (Journal of the Management Sciences, 2024)
The study is purely on promoting peace and reducing conflicts between farmers and herders in Nigeria. The objectives of this study are to assess the challenges, opportunities and solutions in promoting peace and reducing conflicts between farmers and herders in Nigeria; to analyze the root causes of conflicts between farmers and herders in Nigeria; and to determine the challenges faced in promoting peace and reducing conflicts between farmers and herders in Nigeria. This is a conceptualized study. The study is based on the theory of Environmental Economic Theory propounded by Thomas Malthus in 18th century. From Malthus to Neo-Malthusian theories have played a dominant role in the post-cold war conflict and security issues. Findings showed that farmer-herder conflict in Nigeria has its roots deeply embedded in history, dating back several centuries. In the pre-colonial era, Nigeria’s diverse ethnic groups practiced different livelihoods, with farmers engaging in settled agriculture and herders leading nomadic lives, moving their livestock across vast territories in search of grazing lands and water sources. The paper concluded that the rifts between herders and farmers are such that can be eliminated to its nearest minimum. This can only happen when the stakeholders and actors build up structures and processes of mitigating such. The key and core root causes, challenges and peace resolution route has been laid out which are poor governance, cattle theft, security concerns, deep-rooted historical grievances, lack of trust and cultural and linguistic diversity. It is recommended that the government take a lead in resolving conflicts and crisis amongst herders and farmers by ensuring that both actors are not neglected in any aspect but carried along.